(untitled) (Bangladesh Journal of Medical Science, 2024)
The article aims to evaluate safety and effects CR program on physical capacity and QoL in patients after open-heart surgery complicated with sternomediastinitis. This observational cohort study included 104 patients, of them 58 were males and 34 females, who underwent cardiac surgery made by sternotomy. We divided the cohort into two groups: 1st group clustered of 92 patients, who did not have sternomediastinitis complications after the surgery; 2nd group clustered of 12 patients, who had sternomediastinitis complications after the surgery. We assessed following variables: physical capacity using 6-minute walk test (6MWT ) and the metabolic equivalent (MET) and maximal oxygen consumption (VO2max), QoL using SF36 survey. Statistical analyses were performed using the IBM SPSS Statistics software (version 19). The Kolmogorov-Smirnov and Shapiro-Wilk tests were used to check the normality of distributions. Then, the Mann-Whitney U test was performed to compare not normally distributed independent variables, in order to see the difference (significance level was accepted at p<0.05). After that, the Pearson’s two tailed correlation test was used to find the connection between variables of two groups. Properly selected physical exercises during CR improve the fitness and physical activity of patients after sternomediastinitis, as well as, QoL mesures - general health and mental status. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 527-538